2018
DOI: 10.1111/hsc.12621
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of organisation‐wide, trauma‐informed care models in out‐of‐home care (Oo HC ) settings

Abstract: Trauma in early childhood has been shown to adversely affect children's social, emotional, and physical development. Children living in out-of-home care (OoHC) have better outcomes when care providers are present for children, physically, psychologically, and emotionally. Unfortunately, the high turnover of out-of-home carers, due to vicarious trauma (frequently resulting in burnout and exhaustion) can result in a child's trauma being re-enacted during their placement in OoHC. Organisation-wide therapeutic car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 30 publications
(81 reference statements)
0
38
0
Order By: Relevance
“…In sum, a growing body of evidence supports the effectiveness of the CARE program model, a fact that is acknowledged in the scientific rating of 3 (promising research evidence) for CARE in the California Evidence-Based Clearinghouse (http://www.cebc4cw.org/program/children-and-residential-experiences-care/detailed), where CARE is listed under both the Higher Levels of Placement and the Alternatives to Long-Term Residential Programs topics. In addition, a recent review of organization-wide, trauma-informed care models in out-of-home care settings found the design of the CARE evaluation, as reported in , to be the only one of seven studies that met inclusion criteria to have moderate rather than high risk of bias (Bailey et al, 2018). The CARE Evaluation also addressed nearly all of the recommendations for the measurement, analysis, design, and reporting of evaluations of trauma-informed organizational interventions in Purtle's (2018, p. 13) systematic review.…”
Section: Discussionmentioning
confidence: 99%
“…In sum, a growing body of evidence supports the effectiveness of the CARE program model, a fact that is acknowledged in the scientific rating of 3 (promising research evidence) for CARE in the California Evidence-Based Clearinghouse (http://www.cebc4cw.org/program/children-and-residential-experiences-care/detailed), where CARE is listed under both the Higher Levels of Placement and the Alternatives to Long-Term Residential Programs topics. In addition, a recent review of organization-wide, trauma-informed care models in out-of-home care settings found the design of the CARE evaluation, as reported in , to be the only one of seven studies that met inclusion criteria to have moderate rather than high risk of bias (Bailey et al, 2018). The CARE Evaluation also addressed nearly all of the recommendations for the measurement, analysis, design, and reporting of evaluations of trauma-informed organizational interventions in Purtle's (2018, p. 13) systematic review.…”
Section: Discussionmentioning
confidence: 99%
“…The remaining seventy-five papers selected for data extraction contained five systematic reviews which identified definitions and components of TIC relevant to: the juvenile justice system [13]; out-of-home-care [11]; youth inpatient psychiatric and residential treatment settings [10]; inpatient mental health settings [14]; and organisation wide trauma-informed initiatives involving a training component [12]. Twenty-eight of the seventy-five papers were individual studies already included within these systematic reviews.…”
Section: Methodsmentioning
confidence: 99%
“…However, they also noted the absence of research evaluating large-scale TIC efforts, and critically, whether they produced the improved child and family outcomes or future cost savings envisaged. More recent systematic reviews on TIC implementation initiatives in varied settings [10,11,12,13,14] have also highlighted a number of methodological problems within the TIC literature. These include a developing but still relatively limited focus on child and family outcomes; the preponderance of research designs using small samples and lacking a control group; short follow-up periods; high attrition rates; and the inability to disentangle the effects of individual implementation components from broader project outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most interventions have also not been properly evaluated, and there remains a lack of rigorous research examining the impact of these interventions in improving health and/or psychosocial outcomes for children and young people in OoHC 21. Indeed, a recent systematic review investigating the empirical evidence of trauma-informed, organisation-wide models implemented in residential OoHC settings identified three models including The Sanctuary Model, Children and Residential Experiences programme and the Attachment Regulation and Competency framework, and concluded that the evidence base is limited, making it difficult to accurately evaluate outcomes of trauma-informed models 22. Recent studies have outlined the health and psychosocial needs of children and young people in OoHC and the interventions and practice models that have been designed to meet these needs; however, to date, very little research has been focused on evaluating the effectiveness of these interventions 15.…”
Section: Introductionmentioning
confidence: 99%